In vitro screening of putative probiotic strains and prebiotics for effective anti-diarrheal synbiotics formulation - Anand, Santosh; Singla, Varsha; Singh, Jyoti; Mandal, Surajit; Tomar, Sudhir Kumar (Indian Journal of Dairy Science, 2018)
The present study was to investigate the utilization of prebiotics by selected Lactobacillus and Bifidobacterium probiotic strains and antagonistic effect of their potential synergy on enterotoxigenic Escherichia coli (ETEC) as target pathogen. To select the suitable synbiotic combination, in vitro fermentation, antibacterial potential through co-culturing, and toxin production by ETEC in co-cultured condition through GM1 enzyme-linked immunosorbent assay (GM1-ELISA) was examined. All putative probiotic strains grown well in basal media supplemented with fructooligosaccharides (FOS) and galactooligosaccharides (GOS), whereas greater inactivation of ETEC was observed when FOS was used with L. rhamnosus RSI3, GOS with Bifidobacterium breve BIF7 and inulin with Lactobacillus acidophilus NCDC 13. Â All three combinations are shown greater than two log reduction in ETEC population. Also, there was a decrease in LT enterotoxin concentration when ETEC was grown with these synbiotics. Short chain FOS, GOS and inulin were found to be the most effective substrates, depending on its compatibility with different strains improving its antagonistic activity for the development of antidiarrheal synbiotics. These pairs can be used as synbiotic combinations for preparing dairy based fermented formulations against secretory diarrhea.